Irrational Exuberance: Cardiopulmonary Resuscitation as Fetish. Issue 2 (1st February 2017) - Rosoff, Philip M.; Schneiderman, Lawrence J.
Abstract : The Institute of Medicine and the American Heart Association have issued a "call to action" to expand the performance of cardiopulmonary resuscitation (CPR) in response to out-of-hospital cardiac arrest. Widespread advertising campaigns have been created to encourage more members of the lay public to undergo training in the technique of closed-chest compression-only CPR, based upon extolling the virtues of rapid initiation of resuscitation, untempered by information about the often distressing outcomes, and hailing the "improved" results when nonprofessional bystanders are involved. We describe this misrepresentation of CPR as a highly effective treatment as the fetishization of this valuable, but often inappropriately used, therapy. We propose that the medical profession has an ethical duty to inform the public through education campaigns about the procedure's limitations in the out-of-hospital setting and the narrow clinical indications for which it has been demonstrated to have a reasonable probability of producing favorable outcomes.